2006
DOI: 10.1080/17415990600755131
|View full text |Cite
|
Sign up to set email alerts
|

β-Aminocrotononitrile in heterocyclic synthesis: Synthesis of polysubstituted pyridines as precursors to bicycles and polycycles

Abstract: β-aminocrotononitrile (1) reacted with either cyanothioacetamide to give (3) or malononitrile to afford an anion (5). Pyridine-2(1H)-thione (4) was obtained by boiling of (3) in ethanol and Et 3 N or treatment of (5) with H 2 S, respectively. The reaction of anion 5 with isothiocyanates (6) gave N-substituted pyridine-2(1H)-thiones (7). N-Substituted pyridine-2(1H)-thiones (7) can be used for the preparation of pyrido[2,3-d]pyrimidines (8a-e) and (10a-e), or the preparation of pyrido[1,2-a]pyrimidines (12a-d).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The initial synthesis of 20-member alkylamine and 20-member ether libraries, as shown in Scheme 1, began with condensation between 3-aminocrotonitrile (4) and 2-cyanothioacetamide (5) to furnish the aminopyridyl core 6. [16] This was cyclized with a-chloro-p-methoxybenzamide (7) to give the diaminothieno[2,3-b]pyridine scaffold with the p-methoxybenzamide 8. To produce the 20-member amine library, intermediate 8 was reacted with various alkyl chlorides to generate analogues 9 a–p.…”
mentioning
confidence: 99%
“…The initial synthesis of 20-member alkylamine and 20-member ether libraries, as shown in Scheme 1, began with condensation between 3-aminocrotonitrile (4) and 2-cyanothioacetamide (5) to furnish the aminopyridyl core 6. [16] This was cyclized with a-chloro-p-methoxybenzamide (7) to give the diaminothieno[2,3-b]pyridine scaffold with the p-methoxybenzamide 8. To produce the 20-member amine library, intermediate 8 was reacted with various alkyl chlorides to generate analogues 9 a–p.…”
mentioning
confidence: 99%
“…Also the treatment of 6-amino-3,5-dicyano-6-methyl-N-substitutedpyridine-2(1H)-thione (261) with DMF DMA in dry dioxane afforded the corresponding amidine (262) which on boiling with ammonium acetate in (264), respectively, as shown in Scheme 37 [160].…”
Section: Scheme 36mentioning
confidence: 99%
“…One type of reaction, which is potentially valuable for the future purpose, is with 1,3-dicarbonyl compounds (1) to give enamines (2) [4]. (1) 2 We have reported that these enamines (2) were used as precursors in the synthesis of pentasubstituted pyridines (3)(4)(5)(6) [6,7]. The structures of these compounds have been confirmed by X-ray crystallography [6,7].…”
mentioning
confidence: 93%
“…Formamide acetals are useful reagents; [3,4] their main application has been used for functional group transformations [5], but they may also be regarded as one-carbon synthons in the construction of carbon skeletons. One type of reaction, which is potentially valuable for the future purpose, is with 1,3-dicarbonyl compounds (1) to give enamines (2) [4]. (1) 2 We have reported that these enamines (2) were used as precursors in the synthesis of pentasubstituted pyridines (3)(4)(5)(6) [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation